An advertising approach to promote energy drink case study: Gorilla Energy drink / Muhammad Reedha Mat Lizah - Mat Lizah, Muhammad Reedha (2019)
The Gorilla Energy drinks aim to improve performance and hydrate athletes who participated in endurance sports and the use of energy drinks has increased dramatically in recent years, particularly among adolescents and young adults. Energy drinks are marketed on the demand that these products provide increased energy to improve physical and cognitive performance. However, studies supporting this claim are limited. In fact, some harmful effects on health have been linked to energy drinks. This has raised the question of whether this drink is safe. The study was conducted to identify and discuss published articles studying the health effects associated with energy drinks. It is concluded that although energy drinks can have a good impact on physical performance, this product also has a health priority if it is not used. In order to inform target audiences, marketing of energy drinks should be promoted through creative advertising to attract adolescent and young adult intentions. This is because the effect of online food marketing on creative advertising on young adults is not yet clear. This study examines the benefits of energy drink through creative advertising on young teenagers, using energy drinks for example cases. This study shows the power of advertising affecting adolescents while attracting people's health to young adults, who are unaware of the importance of energy drinks.